Deflazacort-induced Acneiform Eruptions - Mohammed Shakeel Mohammed Bashir; Mohammad Saleem; Uday Choudhari (Wolters Kluwer Medknow Publications, 2017)
A 38-year-old male suffering from a low backache since 3 months was diagnosed as a case of L4-L5 disc prolapse after magnetic resonance imaging examination. He was treated with tolperisone, aceclofenac, and paracetamol in these drugs deflazacort added later. From the 2nd day of an addition of deflazacort in the therapy, sharply marginated, infiltrative, and erythematous skin eruptions with discrete itching sensations were seen. It was diagnosed as deflazacort-induced acneiform eruption and treated with doxycycline for 2 months which led to the disappearance of acneiform eruptions.